Palyno-stratigraphy of the lower Karroo sequence in the central Sebungwe District, Mid-Zambezi Basin, Rhodesia - Falcon, Rosemary S (Bernard Price Institute for Palaeontological Research, 1975)
Hart (1962) was the first to discuss seriously the subject "palynology-key to stratigraphy" with regard to Southern Africa. Since then a number of publications have appeared on African Karroo palynology. However, to date only one large scale microfloral zonation scheme has been proposed -that of Hart (1967). In this, four major palynofloristic zones were outlined for Lower Karroo (Permian) sequences, drawn from surface and sub-surface material in South and Central Africa. Another scheme, dividing the Permian into eight zones in S. Africa (Great Karroo Basin) , is as yet unpublished (Anderson, in press). In an attempt to apply palynology to the problems of geological correlation and relative age determinations, specifically in the field of coal exploration in Rhodesia, a standard section in the form of one borehole, the Matabola Flats borehole, well-sited, deep and with apparently continuous deposition was chosen for palynological biostratigraphic analysis. Fifty-five miospore genera and ninety-eight species have been recognised in this study. Their systematic descriptions and statistical analyses are published elsewhere, Falcon 1975 a, b. Detailed analysis of the forty-eight productive samples show large scale micro-floral changes up the stratigraphic column. Four major assemblage zones and eight assemblage sub-zones are herein proposed, thereby expanding by four the palynofloristic zones of Hart.
Keywords: palynology; Beaufort Group; climate change